Alberta's Day Care Controversy: From 1908 to 2009 and Beyond - Tom Langford (Athabasca University Press, 2011)
Day care in Alberta has had a remarkably durable history as a controversial issue. Since the late 1950s, disputes over day care programs, policies, and funding have been a recurring feature of political life in the province. Alberta's Day Care Controversy traces the development of day care policies and programs in Alberta, with particular emphasis on policy decisions and program initiatives that have provoked considerable debate and struggle among citizens. For most of Alberta's first fifty years as a province, day care was treated as a private rather than a public issue. Beginning in the late 1950s, however, debates about day care began to appear regularly on the public record. Dr. Tom Langford brings to light the public controversies that occurred during the last four decades of the twentieth century and the first decade of the new millennium, placing contemporary issues in historical context and anticipating the elements of future policy struggles.